Effects of deep brain stimulation of the cerebellothalamic pathways on the sense of smell - Kronenbürger, Martin; Zobel, S.; Ilgner, J.; Finkelmeyer, A.; Reinacher, P.; Coenen, V. A.; Wilms, Henrik; Kloss, Manja; Kiening, Karl; Daniels, C.; Falk, D.; Schulz, J. B.; et al. (Experimental neurology, 2010)
The cerebellum and the motor thalamus, connected by cerebellothalamic pathways, are traditionally considered part of the motor-control system. Yet, functional imaging studies and clinical studies including patients with cerebellar disease suggest an involvement of the cerebellum in olfaction. Additionally, there are anecdotal clinical reports of olfactory disturbances elicited by electrical stimulation of the motor thalamus and its neighbouring subthalamic region. Deep brain stimulation (DBS) targeting the cerebellothalamic pathways is an effective treatment for essential tremor (ET), which also offers the possibility to explore the involvement of cerebellothalamic pathways in the sense of smell. This may be important for patient care given the increased use of DBS for the treatment of tremor disorders. Therefore, 21 none-medicated patients with ET treated with DBS (13 bilateral, 8 unilateral) were examined with “Sniffin' Sticks,” an established and reliable method for olfactory testing. Patients were studied either with DBS switched on and then off or in reversed order. DBS impaired odor threshold and, to a lesser extent, odor discrimination. These effects were sub-clinical as none of the patients reported changes in olfactory function. The findings, however, demonstrate that olfaction can be modulated in a circumscribed area of the posterior (sub-) thalamic region. We propose that the impairment of the odor threshold with DBS is related to effects on an olfacto-motor loop, while disturbed odor discrimination may be related to effects of DBS on short-term memory.